Generation of single/double Janus emulsion droplets in co-flowing microtube. (April 2019) - Pang, Yan; Du, Yu; Wang, Ju; Liu, Zhaomiao
Highlights: For the single emulsion in this study, the total flow rate of inner phase Q w is control the droplet size and emerging frequency without the effect of Q w1 and Q w2 . The droplet size of the single emulsion droplet follow the predictive relation of flow rate and Ca of continuous phase. In both the single and double emulsion droplets, the droplet size and component fraction can be controlled by the flow rate on demand. Abstract: A novel and facile microfluidic approach for single-step fabrication of W/O Janus droplets and W/O/W double Janus emulsions droplets is developed. The influence of flow rate on the component proportion, size and frequency of the emulsion droplets is experimentally investigated. The proportion of the two components in the droplet is positively correlated with the flow rate ratio of two dispersed phases, Q W1 / Q W2 . In the process of W/O/W double emulsion formation containing two different reagent cores, the droplet diameter changes abruptly because of the translation of droplet generation mode. In the dripping regime, the inner and outer diameters of the double emulsion decrease linearly with the increase of the outer phase flow, and the components of the core droplets remain constant. With the uniform number of cores, the frequency of inner droplet generation is positively correlated with the discrete flow rate, but negatively with the increase of the number of cores.